Calendar symbolism of the Shield of Achilles - Fesenko, A.V. (Archaeoastronomy and Ancient Technologies, 2013)
This article is devoted to a very ancient description of the famous "Shield of Achilles" in the ancient literature. For several centuries this ecphrasis has been actualizing and became an object of imitation. The description of the "Shield of Achilles" is a very broad field for study number of aspects, including calendar symbols. Lights, depicted on the shield, in ancient Greece, mainly, for the calendar objectives and how important calendar celestial cues. A special place in the description of "Shield of Achilles" occupy two cities: "city of the world" and "city of the war". The theme of two cities - the testimony of ancient mythological images of the epoch of the formation of the epic, obviously had a lot of popularity in the second Millennium BC. After Homer Pseudo-Hesiod in "Shield of Heracles" also creates two opposite image of "city of hostility" and "city of marriages". According to the author, the description of these cities can contain a calendar symbols. May be offered two options. First: if the two cities is the symbolism of the two equinoxes, it is just about the division of the year into two parts and the Zodiac into two areas - from the vernal equinox to the autumn (the Upper World) and the autumnal equinox to spring (the Lower World). Second: if there are two Solstice, then we can talk, except for the simple dividing the year into two parts, and the movement of the Sun up from the winter solstice to the summer and down.